Clinical profile of generalized vitiligo patients with associated autoimmune/autoinflammatory diseases. (17th April 2013) - van, N.; Speeckaert, M.; Brochez, L.; Lambert, J.; Speeckaert, R.
Abstract Background The significance of associated autoimmune/autoinflammatory diseases in generalized vitiligo patients with respect to their clinical profile has not yet been completely established. Objective The objective of this study was to evaluate the clinical significance of associated autoimmune/autoinflammatory diseases in generalized vitiligo patients with respect to some general clinical variables, distribution pattern, disease activity and treatment response. Methods Seven hundred generalized vitiligo patients were included in this retrospective observational cohort study. Results Associated autoimmune/autoinflammatory diseases were present in 15.4% of the patient population and were more common in women compared with men, especially concerning thyroid disease. Only vitiligo patients with thyroid disease had clear different clinical characteristics. The percentage of total body surface area involvement was significantly (P = 0.005) higher in the presence of thyroid disease which was more pronounced in women compared with men. Patients with thyroid disease had a particular predisposition to acral and joint depigmentations. No clear differences in disease activity or response to therapy were observed in vitiligo patients with or without autoimmune/autoinflammatory disorders. Conclusion The presence of associated autoimmune/autoinflammatory diseases seems to influence the clinical profile of generalized vitiligo patients. Our results support the hypothesis that in the presence of a thyroid disorder, the disease activity of vitiligo is more extensive, in particular on areas prone to friction.